ENFERMAGEM NA REABILITAÇÃO FÍSICA - Gomes, Joseila S.; Rosanelli, Cleci L. S. P.; Kolankiewicz, Adriane C. B.; Loro, Marli M.; Mertins, Simone M.; Scarton, Juciane (Salão do Conhecimento, 2013)
Resumo